STATUS GIZI PADA REMAJA SMP NEGERI 6 MANADO MENGUNAKAN INDEKS MASSA TUBUH DAN LINGKAR PINGGANG - Pangow, Sofia; Bodhi, Widdhi; Budiarso, Fona (JURNAL BIOMEDIK : JBM, 2020)
Abstract: The influence of nutrition on growth, development, intelligence, and productivity shows the great role of nutrition in human life. Nowadays, Indonesia is facing double nutritional problem, namely the problems of under nutrition and over nutrition. This study was aimed to obtain the profile of nutritional status of students at SMP N 6 Manado (junior high school). This was a descriptive study using a cross-sectional design. Nutritional status was determined by calculating body mass index (BMI) and measuring waist circumference. Respondents were 417 students of grade 1 to grade 3 students. The results showed that based on BMI calculations, 238 respondents (57%) were underweight; 141 respondents (34%) were normal weight; 15 respondents (4%) were overweight; and 23 respondents (5%) were obese. Based on the measurement of waist circumference, there were 23 obese respondents (5%); 9 respondents (2%) were male and 14 respondents (3%) were female. In conclusion, more than 50% of the students at SMPN 6 Manado were underweight, albeit, some students were overweight nad obese.Keywords: teenagers, nutritional status Abstrak: Pengaruh masalah gizi terhadap pertumbuhan, perkembangan, intelektual, dan produktivitas menunjukkan besarnya peran gizi bagi kehidupan manusia. Saat ini, Indonesia menghadapi masalah gizi ganda, yaitu masalah gizi kurang dan masalah gizi lebih. Penelitian ini bertujuan untuk mengetahui status gizi dengan perhitungan indeks massa tubuh (IMT) dan pengukuran lingkar pinggang. Jenis penelitian ialah deskriptif dengan desain potong lintang. Responden ialah siswa kelas 1 sampai kelas 3 di SMPN 6. Hasil penelitian mendapatkan 417 responden. Berdasarkan IMT didapatkan 238 responden (57%) dengan status gizi kurang, 141 responden (34%) dengan status gizi normal, 15 responden (4%) dengan status gizi lebih, dan 23 responden (5%) dengan status gizi obesitas. Pada pengukuran lingkar pinggang didapat 23 responden obesitas (5%), terdiri dari 9 laki-laki (2%) dan 14 perempuan (3%) dengan total responden 417 orang. Simpulan penelitian ini ialah lebih dari 50% siswa SMPN 6 Manado dengan status gizi kurang namun terdapat juga sebagian siswa dengan status gizi lebih dan obesitas.Kata kunci: remaja, status gizi